Effect of Vitex agnus - castus L. leaf and fruit flavonoidal extracts on serum prolactin concentration - M Azadbakht; A Baheddini; S. M Shorideh; A Naserzadeh (Institue of Medicinal Plants, ACECR, 2005)
Background: Vitex agnus - castus is a well known plant in herbal medicine from centuries ago. In Iranian traditional medicine its leaves and fruits are used for increasing milk. Objective: In present research the effects of Vitex agnus - castus leaf and fruit flavonidal extract on serum concentration of prolactin hormone has been investigated. Method: Selective deosages of Vitex agnus - castus were orally administrated to female rats during proestrus stage of estrus cycle and lactation.In the control group of rats distilled water was adminstrated instead of Vitex agnus - castus extract. At each stage (procestrus, and 3rd day of lactation) the animal was anaesthetized by inhalation of ether and fresh blood sample was taken from its heart. The serum was separated by centrifugation. Serum prolactin hormone was measured by RIA (Radio Immuno Assay) method. The data were analysed by ANOVA, MANOVA and LSD test at p < 0.05. Results: Oral administration of 70 mg/kg/day of Vitex agnus - castus extract in lactation stages, significantly increased serum prolactin, compared with the control group of rats. The effect of Vitex agnus - castus extract on the diffrence of sampling weight and starting weight (before administration) was not significant in comparison to the control group rats. Conclusion: It is concluded that results obtained in this research may confirm the use, in tradional Iranian medicine, of this plant, for increased milk Production.